Cersenlau Sugar (Cherry Kersen & Telang Ungu): A Potential Antidiabetic Agent for Pancreatic Beta-Cell Repair in Rats - Cintari, Lely; Budiani, Ni Nyoman; Ningtyas, Listiana Ade Widya (Poltekkes Kemenkes Palu, 2024)
This study aimed to find out the antidiabetic effects of CERSENLAU Sugar (Cherry Kersen & Telang Ungu) on the histological of the pancreas of diabetic rats. Method: The type of research used is purely experimental with a pre-post test control group design. The subject of the study was a male white Wistar rat (Rattus Norvegicus) aged 2-3 months and weighing an average weight of between 150-200 grams. On this plan the subject was randomized and then divided into 2 groups that is normal control and treatment group consisting of 4 subgroups namely: 1. The group diabetes was given commercial sugar diabetes and 3 diabetes groups were given CERSENLAU Sugar with different levels (100 mg/kg Body Weight; 200 mg/ kg Body Weight; 400 mg/Kg Body Weight). Each group consisted of six test animals. The total number of test animals was 30. Kruskall Wallis test to determine the significant differences between the treatment group and the control group with a p-value < 0.05 selected as the degree of significance. Results: CERSENLAU Sugar (Cherry Kersen Telang Ungu) contains phenols (86.63 mg), flavonoids (48.72), vitamin C (45,76 mg/100 ml), sugar (1,11%), anthocyanin (1,64 mg/100ml) and fiber (1,51%). Based on the results of the observations of the histopathology preparation of the pancreatic rat and the analysis carried out, it was proved that the administration of Cersenlau affected the histopathology figure of the pancreas of rats induced by alloxan. But at doses of 200 mg/kg Body Weight and 400 mg/ kg Body Weight, the effect is not very good compared to the dose of 100 mg/kg Body Weight which has a better effect. Conclusion: CERSENLAU Sugar (Cherry Kersen & Telang Ungu) repairs damage to pancreatic beta cells in mice with diabetes mellitus and affects pancreatic tissue regeneration as seen from the level of damage to pancreatic beta cells in animal models of diabetes.